2000
DOI: 10.1046/j.1365-2761.2000.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pathogens in rainbow trout, Oncorhynchus mykiss (Walbaum), reared at Danish freshwater farms

Abstract: During a 2‐year period, bacterial fish pathogens were monitored on five rainbow trout, Oncorhynchus mykiss (Walbaum), freshwater farms in Denmark. A total of 1206 fish were examined and 361 bacterial isolates were identified phenotypically. Enteric redmouth disease, furunculosis and rainbow trout fry syndrome/coldwater disease were recorded. Infections caused by Flavobacterium psychrophilum occurred most frequently, but only one outbreak of enteric redmouth disease caused by Yersinia ruckeri serotype O1 and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 25 publications
6
126
2
1
Order By: Relevance
“…Y. ruckeri strain 100415-1/4 (serotype O1, biotype 2) which was originally obtained from a clinical outbreak of ERM in a freshwater trout farm, was utilized for all challenge studies. The bacterium was identified (19), cultured in Luria-Bertani (LB) broth, and incubated on an orbital shaker at 22°C for 48 h until reaching peak exponential phase, at which time the culture was harvested via centrifugation (at 22°C and 4,000 ϫ g for 10 min) and serial 10-fold dilutions were prepared with sterile phosphate-buffered saline (PBS) to determine the bacterial cell concentration (i.e., CFU) by the plate count method.…”
Section: Methodsmentioning
confidence: 99%
“…Y. ruckeri strain 100415-1/4 (serotype O1, biotype 2) which was originally obtained from a clinical outbreak of ERM in a freshwater trout farm, was utilized for all challenge studies. The bacterium was identified (19), cultured in Luria-Bertani (LB) broth, and incubated on an orbital shaker at 22°C for 48 h until reaching peak exponential phase, at which time the culture was harvested via centrifugation (at 22°C and 4,000 ϫ g for 10 min) and serial 10-fold dilutions were prepared with sterile phosphate-buffered saline (PBS) to determine the bacterial cell concentration (i.e., CFU) by the plate count method.…”
Section: Methodsmentioning
confidence: 99%
“…Unique clones were sequenced and their distribution assessed among 34 strains. The analysis showed that F. psychrophilum is composed of two genetic lineages, possibly reflecting host specificity.Flavobacterium psychrophilum is the causative agent of bacterial coldwater disease and rainbow trout fry syndrome, both of which affect salmonid fish and impact commercial aquaculture and resource enhancement hatcheries worldwide (12,19,21). Coho salmon (Oncorhynchus kisutch [Walbaum]) and rainbow trout (O. mykiss) are particularly susceptible, although F. psychrophilum also infects other fish species (21).…”
mentioning
confidence: 99%
“…F. psychrophilum primarily affects juvenile salmonids and results in high mortality rates among fry and fingerlings in hatcheries. In Europe this bacterium constitutes a large problem for the aquacultural production of rainbow trout (Oncorhynchus mykiss) (5). Outbreaks of the disease are mainly seen at low temperatures, with the most serious problems occurring at temperatures below 15°C (17).…”
mentioning
confidence: 99%